Impact of Light at Night Is Phase Dependent: A Study on Migratory Redheaded Bunting (Emberiza bruniceps) - Kumar, Jayant; Malik, Shalie; Bhardwaj, Sanjay Kumar; Rani, Sangeeta (Frontiers in Ecology and Evolution, 2021)
Artificial light at night (LAN) alters the physiology and behavior of an organism; however, very little is known about phase-dependent effects of LAN, particularly, in night migratory songbirds. Therefore, in this study, we investigated whether the effects of LAN on daily activity and photoperiodic responses in the Palearctic Indian migratory songbird, redheaded buntings (Emberiza bruniceps), is dependent on the different phases of the night. Male buntings maintained under short photoperiod (8L:16D; L = 100 lux, D < 0.1 lux) in individual activity cages were exposed to LAN (2 lux) for 6 weeks either in 4 h bin given at the different phases of 16 h night (early, mid, or late at ZT 08–12, ZT 14–18, or ZT 20–24, respectively; n = 9 each group) or throughout 16 h night (all night light, n = 6, ZT 08–24, the time of lights ON was considered as Zeitgeber time 0, ZT 0). A group (n = 6) with no LAN served as control. The results showed that LAN at the different phases of night induced differential effects as shown by an intense activity during the night, altered melatonin and temperature rhythms, and showed an increase in body mass and body fattening, food intake, and gonadal size. Midnight light exposure has a greater impact on migration and reproduction linked phenotypes, which is similar to the ones that received light throughout the night. The highlights of this study are that (i) LAN impacts day-night activity behavior, (ii) its continuity with the day alters the perception of day length, (iii) birds showed differential sensitivity to LAN in a phase-dependent manner, (iv) the direction of placing LAN affects the daily responses, e.g., LAN in the early night was “accepted” as extended dusk but the late night was considered as early dawn, and (v) midnight LAN was most effective and induced similar responses as continuous LAN. Overall, LAN induces long day responses in short days and shows differential sensitivity of the different phases of the night toward the light. This information may be valuable in adopting a part-night lighting approach to help reduce the physiological burden, such as early migration and reproduction, of artificial lighting on the nocturnal migrants.